THE NECESSITY OF HARMONIZATION AS A GUIDING PRINCIPLE: FOCUSING ON COOPERATIVE LEGISLATION IN SOUTH KOREA - Shin, Changsub (International Journal of Cooperative Law, 2023)
The law, in a broad sense, includes precedents, equity, and custom as well as the will of legislators. From this perspective, the principles and experienses accumulated in the international cooperative movement serve as foundation for creation of a cooperative legal tradition. In terms of the cooperative legal tradition, harmonization presupposes differences, and allows the disconnection and replacement of a paradigm. As shown in the term “paradigm,” harmonization does not mean uniformity between positive laws. Legal theories and concepts function as guiding or interpretation principles in relation to the positive laws through comparison and evaluation of those positive laws. Harmonization means such common legal theory that operates on the principle of interpretation of the cooperative laws in a nation.This study aims to examine how the concepts of cooperative transactions and member shares works in Korean cooperative legislation. The definition of these two concepts refer to the contents of the Principlesof European Cooperative Law (hereinafter referred to as its acronym, PECOL). PECOL focused on the ideal legal identity of cooperatives, drafted by a team of legal scholars, and aimed to describe the common core of European cooperative laws through an incorporated comparative study. My intention was to compare the guiding principles provided by PECOL with Korean cooperative law. Korea has nine cooperative laws including The Framework Act on Cooperatives. The Framework Act on Cooperatives was enacted to function as a general law, all the acts except for the Framework Act on Cooperatives are referred to as a “special cooperative law”.